Culture, grief, group processes and hope in times of pandemic - Cristina Martínez-Taboada Kutz (Forum for Group Psychotherapies and Processes, 2024)
This article aims to reflect on the grief in times of Covid 19 as well as its projection in a specific cultural perspective, such as the Spanish one, and its impact on the group and affective processes of individuals. We consider that analyzing the feelings and emotions of subjects or groups at high risk of complicated grief can favor the subsequent design of specialized and preventive interventions. This assumption arises from the participation in a virtual Symposium on The International Day of Hope and Healing After Loss (June, 2020) in the midst of the pandemic. The experience brought together organizations and leaders in the field. There was a convergence in which therapeutic processes, especially group ones, were nourished by the cultural traits and rituals that distinguish each society. Therefore, we can think that finding hope and well-being in times of pandemic is both a collective and individual path rooted in culture.